Frontal fibrosing alopecia shows robust T helper 1 and Janus kinase 3 skewing. (15th June 2020) - Del Duca, E.; Ruano Ruiz, J.; Pavel, A.B.; Sanyal, R.D.; Song, T.; Gay‐Mimbrera, J.; Zhang, N.; Estrada, Y.D.; Peng, X.; Renert‐Yuval, Y.; Phelps, R.G.; Paus, R.; et al.
Summary: Background: Frontal fibrosing alopecia (FFA) is a scarring alopecia with unclear pathogenesis and a progressive course. The disease has a major impact on patients' quality of life and there is a lack of effective treatment to halt disease progression. Methods: We profiled lesional and nonlesional scalp biopsies collected in 2017 from patients with FFA ( n = 12) compared with scalp biopsies from patients with alopecia areata (AA) ( n = 8) and controls ( n = 8) to evaluate gene and protein expression, including the primary outcome (CXCL9). We determined significant differences between biomarkers using a two‐sided Student's t ‐test adjusting P ‐values by false discovery rate. Results: Significant increases were seen in CD8+ cytotoxic T cells, CD11c+ dendritic cells, CD103+ and CD69+ tissue‐resident memory T cells in FFA and AA vs. control scalp ( P < 0·05), with corresponding significantly upregulated granzyme B mRNA, particularly in FFA ( P < 0·01). In AA, cellular infiltrates were primarily concentrated at the bulb, while in FFA these were mainly localized at the bulge. FFA demonstrated significant upregulation of T helper 1/intereferon (IFN) (IFN‐γ, CXCL9/CXCL10), the Janus kinase/signal transducers and activators of transcription (JAK‐STAT) pathway (STAT1, JAK3) and fibrosis‐related products (vimentin, fibronectin; P < 0·05), with no concomitant downregulation of hair keratins and the T‐regulatory marker, forkhead box P3, which were decreased in AA. The stem cell markers CD200 and K15 demonstrated significantly reduced expression only in FFA ( P < 0·05). Conclusions: These data suggest that follicular damage and loss of stem cells in FFA may be mediated through immune attack in the bulge region, with secondary fibrosis and reduced but still detectable stem cells. JAK/STAT‐targeting treatments may be able to prevent permanent follicular destruction and fibrosis in early disease stages. Abstract : What is already known about this topic? Frontal fibrosing alopecia (FFA) has a rising prevalence and currently lacks effective therapeutic options. While FFA is considered to have pathomechanisms similar to lichen planopilaris, underlying immune polarization in FFA is largely unknown, hindering development of targeted treatments. What does this study add? FFA lesional and even nonlesional scalp showed robust immune activation, with CD8+ cytotoxic T cells juxtaposed to follicular stem cells, increased interferon‐γ production and Janus kinase/signal transducers and activators of transcription (JAK/STAT) signalling, and concomitant upregulation of many fibrosis markers. Unlike alopecia areata, FFA is characterized by active production of hair keratins and increased regulatory T cells. Our results suggest that Tc1 T cells may mediate follicular damage and subsequent fibrosis in FFA. What is the translational message? FAA may result from T helper 1/JAK-STAT‐mediated follicular damage and concomitant fibrosis. Early therapeutic targeting of this pathway may have the potential to prevent disease progression.